Protecting olive trees from a deadly disease. (Research'eu results magazine)
The EU-funded XF-ACTORS project recently reported on its disease modelling work, key to its integrated management strategy to control the spread of the Xylella fastidiosa pathogen, which is putting olive groves at serious risk in Southern Italy.